Pengaruh Kualitas dan Harga Tiket Konser K-Pop Terhadap Loyalitas Penggemar yang Dimediasi oleh Kepuasan Penggemar - Fatma Nur Azizah; Susila, Ihwan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of ticket quality and price of KPOP concerts on fan loyalty, with fan satisfaction as a mediating variable. The quantitative method using a positivist approach was employed, with purposive sampling based on a Likert scale questionnaire. Data analysis included validity and reliability tests, classical assumption tests, and multiple linear regression to examine variable relationships. Results indicate that ticket quality positively and significantly affects fan loyalty, while ticket price does not directly affect loyalty significantly. However, ticket price has a positive and significant effect on fan satisfaction, whereas ticket quality does not. Fan satisfaction significantly mediates the relationship between ticket price and loyalty but not for ticket quality. This study’s limitations include the population scope and data collection methods, which may affect generalizability. It is recommended that organizers focus on improving event quality and fan satisfaction to maintain loyalty. Future research should expand variables and research methods to enhance understanding.